2013
DOI: 10.1093/humrep/det089
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mullerian hormone levels in girls and adolescents with Turner syndrome are related to karyotype, pubertal development and growth hormone treatment

Abstract: what is known already: Most girls with TS suffer from incomplete sexual development, premature ovarian failure and infertility due to abnormal ovarian folliculogenesis. Serum AMH levels reflect the ovarian reserve in females, even in childhood. study design, size, duration: Cross-sectional study investigating 270 karyotype proven TS patients aged 0-20 years between 2009 and 2010. participants/materials, settings, methods: Studies were conducted at three University Children's hospitals in Europe. Main outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
64
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 46 publications
13
64
1
5
Order By: Relevance
“…Indeed, comparable live birth rates have been reported with the use of fresh or cryopreserved embryos (15). Protocols and methods of egg retrieval are identical for oocyte and embryo freeze cycles.…”
Section: Embryo Cryopreservationmentioning
confidence: 84%
See 1 more Smart Citation
“…Indeed, comparable live birth rates have been reported with the use of fresh or cryopreserved embryos (15). Protocols and methods of egg retrieval are identical for oocyte and embryo freeze cycles.…”
Section: Embryo Cryopreservationmentioning
confidence: 84%
“…However, the paucity of available data on AMH during childhood accounts for the need to interpret its values in this population with caution (14). Visser et al (15) recently studied serum AMH levels in girls and adolescents with TS and reported detectable values of this peptide in 21.9% of patients, the results correlating with karyotypes. In addition, AMH was detected in 77% of girls with 45,X/46,XX karyotypes, but in only 10% of those with 45,X karyotypes.…”
Section: Fertility Preservation Optionsmentioning
confidence: 99%
“…AMH appears to be a reliable marker in this field, and is associated with karyotype as well as with ovarian function, the lowest AMH levels being found in 45,X monosomy patients and in those with no signs of spontaneous puberty [22,23]. AMH has been found to predict disturbance at puberty onset in young TS girls and premature ovarian failure in adolescent and adult TS patients [22][23][24]. Nevertheless, none of the cited studies proved the superiority of AMH over FSH in predicting spontaneous puberty.…”
Section: Discussionmentioning
confidence: 99%
“…Based on an analysis of 15 girls, Lunding et al [24] confirmed that an AMH level below -2 SD (4 pmol/L) predicted failure to enter puberty. However, a strong negative correlation between AMH and FSH was found in a multicentre study, but due to its cross-sectional design the authors stressed the need for a longitudinal study to determine if AMH at a younger age is predictive and whether multiple measurements are needed over time [23].…”
Section: Discussionmentioning
confidence: 99%
“…Turner Syndrome AMH levels can serve as a useful marker of the follicle pool in patients with Turner syndrome. AMH levels in these patients are related to karyotype, pubertal development and growth hormone treatment (25). A low AMH level can predict failure to enter puberty in young patients and imminent POF (26).…”
Section: Premature Ovarian Failure (Pof)mentioning
confidence: 99%